Cost-benefit analysis and technical efficiency evaluation of full-scale membrane bioreactors for wastewater treatment using economic approaches. (10th June 2021) - Gao, Tingwei; Xiao, Kang; Zhang, Jiao; Zhang, Xiaoping; Wang, Xiaomao; Liang, Shuai; Sun, Jianyu; Meng, Fangang; Huang, Xia
Abstract: While the membrane bioreactor (MBR) technology has been broadly applied to treat wastewater, a rational assessment of its techno-economy is required for its sustainable development. In this study, we performed cost-benefit analysis (CBA) and data envelopment analysis (DEA) of 35 large-scale MBRs (each with a treatment capacity of ≥10, 000 m 3 /d). Based on the investment and operation data, we evaluated the marginal cost and environmental benefit (as a function of the shadow prices of pollutants) and hence obtained the net profit (averagely ∼35 CNY/m 3 or ∼4.9 USD/m 3 ). According to the non-radial directional distance function (NDDF) approach in the DEA framework, the average cost efficiency and energy efficiency of the MBRs were 0.77 and 0.66, respectively. The distributions of the net profit and cost/energy efficiencies significantly varied according to the geographical location, effluent standard, and operating year of the MBRs as indicated by the results of nonparametric tests. Economic panel modeling showed that the cost/energy efficiencies were also affected by external factors such as regional economic level and population density. The techno-economy of MBRs is prominent on occasions of strict effluent standards and underground locations, and could be improved by further technological advancements and policy incentives. Graphical abstract: Image 1 Highlights: Techno-economy of full-scale MBRs was assessed via economic CBA and DEA approaches. The net profit (= total costs − environmental benefits) was averagely ∼35 CNY/m 3 . The average cost efficiency and energy efficiency were 0.77 and 0.66, respectively. Internal factors such as effluent standards affected the net profit and efficiency. External factors such as regional economy affected the cost or energy efficiency.